Pseudomonas syringae pv. syringae Associated With Mango Trees, a Particular Pathogen Within the “Hodgepodge” of the Pseudomonas syringae Complex - Gutiérrez-Barranquero, José A.; Cazorla, Francisco M.; de Vicente, Antonio (Frontiers in Plant Science, 2019)
The Pseudomonas syringae complex has been used for decades as a “hodgepodge,” including many taxonomically-related species. More than 60 pathovars of P. syringae have been described based on distinct host ranges and disease symptoms they cause. Our particular study began in early 1990s, when bacterial apical necrosis (BAN) of mango trees, a critical disease elicited by P. syringae pv. syringae in Southern Spain, was described for the first time. P. syringae pv. syringae exhibits important epiphytic traits and virulence factors, which may promote its survival and pathogenicity in mango trees. P. syringae pv. syringae strains isolated from mango trees have been investigated to elucidate the mechanisms that governs their epiphytic and pathogenic lifestyles. The majority of P. syringae pv. syringae isolated from mango trees produce an antimetabolite toxin, called mangotoxin, whose leading role in virulence has been clearly demonstrated. Moreover, phenotypic, genetic and phylogenetic approaches support that P. syringae pv. syringae producers of BAN symptoms on mango trees all belong to a single phylotype within phylogroup 2, are adapted to the mango host, and produce mangotoxin. A genome sequencing project revealed the presence of other factors that may play major roles in its different lifestyles, such as the presence of two different type III secretion systems, two type VI secretion systems and an operon for cellulose biosynthesis. The role of cellulose in increasing mango leaf colonization and biofilm formation, and impairing virulence of P. syringae pv. syringae, suggests that cellulose may play a pivotal role with regards to the balance of its different lifestyles. 62 KB plasmids belonging to the pPT23A-family of plasmids (PFPs) have been strongly associated with P. syringae pv. syringae strains that inhabit mango trees. Complete sequence and comparative genomic analyses revealed major roles of PFPs in detoxification of copper compounds and ultraviolet radiation resistance, both improving the epiphytic lifestyle of P. syringae pv. syringae on mango surfaces. Hence, in this review, we summarize the research that has been conducted on P. syringae pv. syringae by our research group to elucidate the molecular mechanisms that underpin the epiphytic and pathogenic lifestyle on mango trees.